Rheological behavior of polyolefins during UV irradiation at high temperature as a coupled degradative process. (November 2015) - Marek, Adam A.; Verney, Vincent
Graphical abstract: Highlights: We showed the differences in the rheological behavior of PP, HDPE and LDPE. The temperature and UV in situ effects were determined in photorheology experiments. The competition between chain scissions and crosslinking was observed. UV mercury lamp and UV LED were used as irradiation source and gave similar results. Abstract: The photo-rheology method was applied to determinate the differences in the rheological behavior of selected polyolefins (PP, HDPE and LDPE) over a range of temperatures, higher than melting temperatures (160–200 °C) and during UV irradiation as a coupled degradative conditions in air atmosphere. Both, UV mercury lamp and UV LED were used as irradiation source. Multiwave experiments were performed and viscoelastic data were plotted in the complex plane to obtain Cole–Cole plots at different conditions. It helped to assess the molecular evolution of the examined materials. The competition between chain scissions and chain recombination (crosslinking) was observed. Chain scission reactions occurred in PP and for HDPE and LDPE crosslinking reactions predominated, especially over 180 °C. UV irradiation intensified these effects. In the case of HDPE chain scission reactions were also observed especially below 180 °C in processes performed without UV. At higher temperature and under UV irradiation crosslinking reactions and increase of viscosity began to dominate. Despite different energy and emission spectra of irradiation sources, the similar effects were observed.